Ghrelin in the pilosebaceous unit: alteration of ghrelin in patients with acne vulgaris - Cicek, Demet; Demir, Betul; Erden, Ilker; Kuloglu, Tuncay; Ucer, Ozlem; Aydin, Suleyman; Kalayci, Mehmet (John Libbey Eurotext Ltd, 2015)
Background: Ghrelin in the pilosebaceous tissues of human skin and ghrelin levels in patients with acne vulgaris have not yet been investigated. Objective: The purpose of this study was to screen ghrelin immunoreactivity by immunohistochemistry in human pilosebaceous tissues of human skin and also to determine the quantities of ghrelin in the serum of the patients with acne vulgaris. Methods: 30 patients presenting with acne vulgaris and 30 control subjects participated in this study. Ghrelin levels were determined by enzyme linked immunosorbent assay (ELISA). Human hair follicles and sebaceous glands were immunohistochemically examined. Results: Immunohistochemistry results showed that there is a strong ghrelin immunoreactivity in the hair follicles and sebaceous glands in sections of human skin. The mean serum ghrelin levels (27.58 +/- 15.44 pg/mL) in patients with acne vulgaris was significantly lower than those of controls (35.62 +/- 20.46 pg/mL). Conclusions: Ghrelin produced in hair follicles and sebaceous glands of the skin might participate in the pathogenesis of acne vulgaris and also acne vulgaris in humans might be associated with decreased serum ghrelin.
Keywords: acne vulgaris; antimicrobial; ghrelin; pilosebaceous unit